The Tools of Policy Formulation: Actors, Capacities, Venues and Effects - Andrew J. Jordan; John R. Turnpenny (Edward Elgar Publishing, 2015)
Policy analysts are accustomed to thinking in terms of tools and instruments. Yet an authoritative examination of the tools which have been developed to formulate new policies is missing. This book is the first of its kind to distinguish the defining characteristics of the main policy formulation tools, and offer a fresh way of understanding how, why and by whom they are selected, as well as the effects they produce in practice.
Keywords: 330; Public Policy; government; tools; public administration; public management; assessment; policy appraisal